Pengaruh E-Service Quality dan E-Recovery Service Quality melalui Perceived Value terhadap Loyalty Intentions (Studi Kasus: Pengguna Aplikasi Traveloka) - Dwi Adi Widya Tama; Widhy Hayuhardhika Nugraha Putra; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Traveloka is an e-commerce company that operates in the field of hotel reservations and tickets online. In 2018 Traveloka was able to win the Top Brand Award as the first choice of users as an airline ticket reservation, travel and hotel site. However, the various features offered by Traveloka are still not able to provide convenience to its users. Various user complaints can be seen in the Google Playstore, such as the Traveloka application, there are still frequent errors, difficulties in returning funds, failure of transactions, and various other complaints. Analysis of the quality of Traveloka services is a research objective to find out the loyalty of its users. The variables used were e-recovery service quality, e-service quality, loyalty intentions, and perceived value. The sample of this study was 105 users of Traveloka application using non probability sampling as the method and purposive sampling technique in Traveloka application users who had transacted on tickets and hotels. The instrument used in this study used a questionnaire. Multiple linear regression is used to determine the relationship between variables in the hypothesis. The results of this study indicate that e-recovery service quality and e-service quality do not have a significant effect on loyalty intentions through perceived value. E-recovery quality and e-service quality have a significant effect on perceived value. E-recovery service quality, e-service quality and perceived value independently significantly influence loyalty intentions.